He’s just content to sit: a qualitative study of mothers’ perceptions of infant obesity and physical activity - Dinkel, Danae (BMC Public Health, 2017)
BACKGROUND: Rates of obesity among children ages zero to five are rapidly increasing. Greater efforts are needed to promote healthy behaviors of young children. Mothers are especially important targets for promoting health as mothers’ views play a vital role in helping their children foster healthy habits from an early age. Research has found parents’ views of infants’ weight may influence their feeding practices; however, limited research has explored mothers’ view of infants’ weight in relation to the promotion of physical activity. Therefore, the purpose of this study was to explore the perceptions of mothers of normal weight infants and overweight infants about their infant’s weight and physical activity. METHODS: Semi-structured interviews were conducted with mothers of normal weight (n = 18) and of overweight (n = 11) infants (6.5 ± 0.5 month) in a Midwestern city in the United States. A thematic analysis was used to analyze the data. RESULTS: A majority of mothers thought infants could be overweight. However, no mothers referenced their own infant as overweight. Mothers most commonly noted infants could be overweight only if they were formula fed and/or were overfed, not if they were breastfed. Mothers views were not negatively influenced by others who mentioned that their child was either “big” or “small” and only one mother had been told her infant was overweight. A majority of mothers thought an infant could be physically active. When discussing infant activity, mothers primarily referred to it in terms of general mobility and a few thought activity level was related to a personality characteristic. Mothers intended to promote physical activity in the future either through outdoor play or specific organized activities such as sports. Despite a majority of mothers stating they were currently physically active themselves, only a few talked about interacting with their infant to promote their infant’s physical activity. CONCLUSIONS: Efforts are needed by healthcare professionals and other public health professionals to inform mothers about the dangers of increased weight during infancy as well as the importance of interacting with infants to promote physical activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-017-4503-5) contains supplementary material, which is available to authorized users.